Physiochemical Analysis of Drinking Water and Treatment with a Homemade Filter: A Case Study of Illu Abba Bor Zone, Ethiopia. (31st December 2022) - Gudeta, Badhane; Ratnam, M. Venkata; Mohan, Raja
Abstract : The drinking water quality was evaluated in order to provide a continuous supply of clean and safe drinking water for the preservation of public health. The study area consists of three villages: Tulube, Seddo, and Serdo, all of which are located near Mettu town, which is about 550 kilometers south-west of Ethiopia's capital, Addis Ababa. The physical and chemical parameters of the collected drinking water samples were assessed, including pH, turbidity, conductivity, total suspended solids (TSS), total dissolved solids (TDS), and the presence of heavy metals. The samples were examined in the laboratory, and the findings were compared to the World Health Organization (WHO) standards. Almost all of the physiochemical indicators were safe and within the permissible limit for drinking water quality. However, lead ion concentrations were found to be above the WHO standards. An adsorbent produced from banana pseudostems was used to remove lead ions from drinking water. The equilibrium parameters were determined using the Langmuir adsorption isotherm. The drinking water was treated for 4 h in a homemade adsorption column composed of filter medium (sand, charcoal, and powder of treated banana pseudostem). The data revealed that lead ions removal was nearly 70%, but still above the WHO standards.